(untitled) (Proceedings of the International Conference on Gender and Sexuality, 2023)
Whilst considerable progress has been made to advance gender equality in South Africa, particularly in the modern democratic governance space, traditional leadership has remained relatively less responsive to calls for gender inclusion. Yet, women’s participation in decision-making does not only have historical footprints in Africa, as espoused in much of the literature; it also has a potential to facilitate better performance of traditional authority and local municipalities and promote more credible and accountable local government. Although the literature advances several reasons to explain the near exclusion of women’s participation in traditional leadership in the country, this paper argues that the primary factor associated with gender inequality in traditional leadership in South Africa is patriarchy. The paper maintains that patriarchy is a common denominator of much of the explanation for gender inequality in traditional leadership. It is argued, therefore, that understanding the gender issue from this perspective and the sustained yet routinized and systemic ways in which, through patriarchy, women are discriminated against, is critical to promoting women’s participation in traditional leadership.The article relies on secondary data derived from a review of local and international peer-reviewed journals and research reports, including dissertations and databases of research and relevant public institutions. The data was scrupulously analysed and cross-checked to offset the disadvantages of secondary data to ensure credibility of the sources and data reliability and consistency. The article confirms that women’s participation in traditional leadership is constrained by patriarchal biases against women and that promoting women’s participation in decision-making in that institution of governance will evidently enhance performance of local government and quality of life in rural communities. The article concludes that attempts to promote gender equality in traditional leadership should not only focus on legal and administrative precepts but also the development of positive human factor, particularly among members of royal families and tribal communities.